AHP-based analysis of the risk assessment delay case study of public road construction project: An empirical study - Putri Zulaiha, Razi; Mohamad Idris, Ali; Noram Irwan, Ramli (Taylor's University, 2019)
This study proposes an empirical study of risk assessment module for public road construction projects. A case study of a conventional road construction project for new road access for a university that is located in East Coast Malaysia is adopted in this study. Seven delay factors and twenty-two sub-factors were designated from a review of literature and consultations with public road experts. The designate pair-wise questionnaire survey was distributed to the road project team in accordance with the Analytic Hierarchy Process (AHP) technique. The delay risk was assessed quantitatively by prioritizing the risk delay factors and conducting sensitivity analysis in determining the critical construction phase. This study identified the top five most prioritized factors as follows: technical (0.242), natural hazard (0.208), economic and financial (0.186), contractual (0.125), and socio-politics (0.105). The global weight obtained was ranked and the top-five of most prioritised sub-factors were determined as follows: fund risk (0.111), flood (0.099), heavy rain (0.092), unforeseen ground condition (0.086), and existing utility issue (0.076). Sensitivity analysis simplified from Expert Choice 11 programme revealed that the construction phase captured most of the risk, followed by project inception (planning stage), project design, and finally, project completion.